Antarctus Holthuis 2002, n. gen. - Holthuis, Lipke B. (Zenodo, 2002)
Genus Antarctus n. gen. TYPE AND ONLY SPECIES. — Scyllarus mawsoni Bage, 1938 by present designation. ETYMOLOGY. — From the Greek antarktikos (southern), latininized to antarcticus , shortened to provide the ending - arctus , based on the generic name Arctus De Haan, 1849. The name is given to indicate that this is the most southern of the scyllarid genera, its range extending closest to the Antarctic. DIAGNOSIS. — Carapace with rostral, pregastric, gastric and cardiac teeth. Abdomen without arborescent markings; somites II to IV each with a transverse groove and a median longitudinal carina. The tips of pleura II to IV are acute and directed somewhat back. Fourth segment of antenna with two strong oblique carinae; the inner of these traversing the segment from the base to the apex. The anterior margin of this segment with five to eight teeth, the inner two largest; the outer margin has two (or one) large teeth. The pereiopods 2 to 5 are slender, without fringes of long hairs. On the anterior margin of the thoracic sternum the two anterolateral teeth form a deep sharply V-shaped median incision. DISTRIBUTION. — S and E coast of Australia from Eucla, Western Australia to Port Stephens, New South Wales. REMARKS A more extensive discussion of the type species will be given in a work in preparation by Dr John C. Yaldwyn. : Published as part of Holthuis, Lipke B., 2002, The Indo-Pacific scyllarine lobsters (Crustacea, Decapoda, Scyllaridae), pp. 499-683 in Zoosystema 24 (3) on page 528, DOI: 10.5281/zenodo.4689240